Cover Picture: Global Reaction Pathways in the Photodissociation of I3− Ions in Solution at 267 and 400 nm Studied by Picosecond X‐ray Liquidography (ChemPhysChem 16/2013). Issue 16 (31st October 2013) - Kim, Kyung Hwan; Ki, Hosung; Oang, Key Young; Nozawa, Shunsuke; Sato, Tokushi; Kim, Joonghan; Kim, Tae Kyu; Kim, Jeongho; Adachi, Shin‐ichi; Ihee, Hyotcherl
<x xml:space="preserve">Abstract</x> Time‐resolved X‐ray liquidography (TRXL) is a powerful tool for revealing the structural dynamics of chemical reactions in solution. By recording the difference scattering pattern at various time delays between ultrashort laser and X‐ray pulses this technique allowsto collect information on the structural change of the reacting molecules. This is shown by H. Ihee et al. on p. 3687, who elucidate the reaction mechanism of the photodissociation of I3− in solution. In addition to the reaction dynamics of the solute species, the transient structure of the solute/solvent cage and the changes in solvent density and temperature are revealed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>